Factors Affecting Water Soluble Polysaccharide Content and Pasting Properties of Thai Glutinous Rice - Vipa Surojanametakul; PatchareeTungtrakul; Warunee Varanyanond (Agriculture and Natural Resources, 2006)
The effect of milling time, flour milling process, and storage time on the content of water soluble polysaccharides (WSP) and the pasting properties of three Thai glutinous rice varieties (RD6, RD10, and Sanpatong) were evaluated. The results showed that WSP content varied by rice variety. Unpolished RD6 rice contained the highest WSP followed by RD10 and Sanpatong, respectively. Glutinous flour prepared from grain with longer milling time had lower (p<0.05) WSP content. Drymilled glutinous rice flour exhibited higher WSP content and higher peak viscosity than wet milled flour. For milled glutinous rice stored in Nylon bags at room temperature, the WSP content tended to decrease during the first 3 months of storage and then stabilize thereafter. Higher Peak viscosity of glutinous rice flour was obtained in either flour with WSP portion or in the flour added with α-amylase inhibitor (10mM CuSO4).These finding might be useful for Thai glutinous rice flour production and its widely application use.